2019
DOI: 10.15587/1729-4061.2019.184645
|View full text |Cite
|
Sign up to set email alerts
|

Determining mechanical properties of a pressure fire hose the type of «T»

Abstract: Представлені експериментальні дослідження з визначення механічних властивостей (пружних та дисипативних) напірного пожежного рукава типу «Т» із внутрішнім діаметром 66 мм в умовах статичного навантаження. Експеримент проведено на дослідній установці, яка дає можливість заміру сили та деформації. В ході роботи проведено низку натурних експериментів на розтяг зі зразком в умовах статичних циклів навантаженнярозвантаження. Випробування складались з 5 циклів (режими) навантаження-розвантаження, які проводилися із … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…For these reasons, the research results shown in paper [12] cannot be used in the process of diagnosing the technical condition of the PFH. Similar studies were conducted in paper [13]. The segments of the PFH of the "T" type with the internal diameter of 66 mm were used as samples.…”
Section: Literature Review and Problem Statementmentioning
confidence: 94%
See 2 more Smart Citations
“…For these reasons, the research results shown in paper [12] cannot be used in the process of diagnosing the technical condition of the PFH. Similar studies were conducted in paper [13]. The segments of the PFH of the "T" type with the internal diameter of 66 mm were used as samples.…”
Section: Literature Review and Problem Statementmentioning
confidence: 94%
“…Taking into consideration the experimental data, the elasticity module at stretching the NPR material in the longitudinal direction was determined. In article [13] it was found that under the influence of static load, there was a change in the physical properties of the material and the occurrence of residual deformation. The peculiarity of this process is its reverse character, that is, a partial restoration of the physical properties of the material from which the PFH is made after a certain time of the unloading cycle.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the use of extinguishing substances and the methods of their delivery for firefighting are considered in [9]. The issue of preliminary preparation for the use of remote fire extinguishing measures is discussed in [10,11]. The nature of the hazards that must be taken into account when deploying the firefighting equipment is studied in [12].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…At the initial stage, it was decided to illustrate such studies on a geometric model. Thus, as a result of reviewing published data [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], issues that have not yet been studied by other authors were identified. This has allowed us to formulate the following study line: suggest a new method of delivering extinguishing substances in a dumbbell-shaped container to a remote area.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%